(3OjhGf GHf GdeYdes - (3GdgQKj, GHf GdeYde, eMeO Hf Ydj Hf aGQS, J(B592(3g`s
(3ChdgG (B:s
(3eG hbaI GdMGOj Ydi HjQjf (B*** (3hgh GdNdj ef GdXHGA GdYjf , EdG djefMfj LhG hjRjOfj (B*** (3eQVG Ydi eQV hdG jHQjfjs
(3BNQgG (B:s
(3CbdH efc WQaj aj SeGA (B*** (3hEf WdYJ chGcHgG NUGdG, hCYLH efc cja bOQJ JfTC (B*** (3hbO CYWjJ aj GdegO GdceGdGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 279s
(3eYLe GdeDdajf(B: 3 / 525s
(3cTa GdXfhf(B: 1 / 768s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs